The Interplay of Technology Entrepreneurs and Regulation in a New Industry: The Case of the Drone Industry - Giones, Ferran; Gurses, Kerem; Brem, Alexander (Handbook of Research on Techno-Entrepreneurship - Ecosystems, Innovation and Development, 2019)
Technological innovations open opportunities for new entrants (techno-entrepreneurs) to transform and recreate industries, as they come as so called “innovation shocks”. These shocks can change technology trajectories and make irrelevant existing regulatory frameworks. It is unclear, however, what is the interplay between technology evolution, entrepreneurship, and regulation. We explore the case of the drone industry emergence to extract insights on how different profiles of new entrants respond to distinct regulatory frameworks, aiming to decipher the effect that those have on the exploration and development of new tech-based innovation opportunities. Our findings suggest that more attention should be given to the impact that regulatory responses can have on the short and long term development of emerging technological fields. We propose a process framework to make sense of the possible outcomes of distinct regulatory responses, elaborating on the consequences it has on entrepreneurial activity and overall market growth.
CRIS-Team WoS Importer:2021-10-18
Keywords: Technology Entrepreneurship